Urine pH Value and Bacteriology in Purple Urine Bag Syndrome - Yu-Jang Su; Hsiu-Wu Yang; Chen-Wang Chang (Dubai Medical Journal)
Background: Purple urine bag syndrome (PUBS) is an unusual phenomenon in patients with urinary tract infections. The urine of most of these patients has an alkaline pH. Objective: The goal of this study was to identify infectious bacteria and determine urinary pH in patients with PUBS and to evaluate their correlation. Methods: PubMed was searched using the term “Purple urine bag syndrome (PUBS)” for studies on this condition published from October 1980 to September 2019. Sixty-seven patients were identified and divided into those with urine cultures positive for Gram-positive bacteria (GPB; n = 3), Gram-negative bacteria (GNB; n = 45), and mixed Gram-positive and Gram-negative bacteria (MGPNB; n = 19). Age, gender, urinary pH, comorbidities (diabetes and uremia), fever, shock, and mortality were compared in the 3 groups. The correlation between urinary pH and type of bacteria in urine cultures was assessed by regression analysis. Results: Presentation of fever in PUBS accounted for 66.7, 11.1, and 5.3%, p < 0.05, in GPB, GNB, and MGPNB. Regression analyses showed that Pseudomonas aeruginosa was associated with less alkaline urine (regression coefficient −0.936, p < 0.05), whereas Proteus spp. was associated with more alkaline urine (regression coefficient 0.489, p = 0.04). GNB were the most predominant pathogens in patients with PUBS. Conclusion: In PUBS, urine pH and symptom presentation are different by variable bacteria. Fever is associated with urinary GPB. Proteus spp. correlates with more alkaline urine, whereas Pseudomonas spp. correlates significantly with less alkaline urine.